IBU CERDAS UNTUK GENERASI EMAS: STRATEGI JITU DI ERA DIGITAL UNTUK MEMBENTUK ANAK YANG HANDAL - Mirna Agustina; Iftitahul Aini; Lutfia Zaina; Saiful Anwar (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
Abstract: The rate of development of digital technology, which is increasing from time to time has a positive impact on all aspects of life. However, it cannot be denied that it also has a negative effect. Technology crime is a threat to parents, especially mothers. How not, with all kinds of technological developments that make a sophisticated family especially mothers, play the most significant role to guard their children into reliable children by forming children's self-defense. As the first and foremost educator, a mother is required to be a smart mother. Therefore, through this paper, the author seeks to initiate a precise strategy for a mother to form a reliable child. The plan is in the form of direction, training, assignment, habituation, escort, and example. This is important for the child's learning process to instill values and character. The mother is not only required to teach her child to critically understand the media so that it is not consumed by hoaxes but also wise in their use. Related to this, the author conducted library research to realize this strategy so that it can be a solution for optimizing intelligence and character of children in the digital era and being able to maintain family institutions as superior community miniatures.Keywords: Strategy; Self Defense; Gadgets; Digital Era.